+0  
 
0
48
2
avatar

2x+3y=13
12x-3y=-2

Guest Sep 29, 2017
Sort: 

2+0 Answers

 #1
avatar
+1

Solve the following system:
{2 x + 3 y = 13 | (equation 1)
12 x - 3 y = -2 | (equation 2)

Swap equation 1 with equation 2:
{12 x - 3 y = -2 | (equation 1)
2 x + 3 y = 13 | (equation 2)

Subtract 1/6 × (equation 1) from equation 2:
{12 x - 3 y = -2 | (equation 1)
0 x+(7 y)/2 = 40/3 | (equation 2)

Multiply equation 2 by 6:
{12 x - 3 y = -2 | (equation 1)
0 x+21 y = 80 | (equation 2)

Divide equation 2 by 21:
{12 x - 3 y = -2 | (equation 1)
0 x+y = 80/21 | (equation 2)

Add 3 × (equation 2) to equation 1:
{12 x+0 y = 66/7 | (equation 1)
0 x+y = 80/21 | (equation 2)

Divide equation 1 by 12:
{x+0 y = 11/14 | (equation 1)
0 x+y = 80/21 | (equation 2)

x = 11/14               and                      y = 80/21

Guest Sep 29, 2017
 #2
avatar+77092 
+1

2x+3y=13  ⇒   3y   = 13 - 2x      (1)
12x-3y=-2 ⇒    3y  =   2 + 12x    (2)

 

Set (1)  = (2)

 

13 - 2x  =  2 + 12x     add 2x to both sides, subtract 2 from  both sides

 

11   = 14x         divide both sides by 14

 

11/ 14  = x

 

Putting this into (1), we have

 

3y  = 13 - 2 (11/ 14)

3y  = 13  - 11/7           get a common denominator    

3y  = 91/7 - 11/7

3y  = 80/7          divide both sides by 3

y  = 80/ 21

 

 

cool cool cool

CPhill  Sep 29, 2017

16 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details